Ethical Reflections on the Boundaries of Moral Indifference -To what extent are we responsible for others? - Lv, Wenyu (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
When the lines between moral indifference and indifference blur, it is easy to fall into one of two misunderstandings. it is easy to fall into one of two misunderstandings: moral nihilism or moral disenchantment. If we define moral indifference as any behavior, it tends to lead to moral nihilism. If we define any behavior as non-moral indifference, moral indifference is susceptible to moral disenchantment. Only a clear delineation of the boundaries of moral indifference can aid in the dissipation of the phenomenon. Moral indifference is a moral judgment, a moral psychological behavior, and a social phenomenon. Effectively addressing the boundary issue of moral indifference is a key way to mitigate moral indifference. Specifically, collaborative governance is an effective mechanism for dealing with moral crises, contractual governance is an important channel for upholding moral authority, and network governance is a preferred choice for shaping a moral community.